Reactivity and Adaptability: Applying Gender and Age Assessment to the Leader Resilience Profile® - Reed, Diane E.; Reedman, Ashley E. (Frontiers in Education, 2020)
Turbulent events in leadership, and in life, can challenge even those most stoic in the face of adversity and loss. Prefacing with a combined definition of resilience, this paper illustrates the complete life cycle of resilience in the face of adversity, and its resultant rewards when and if appropriately applied. Phases included in this life cycle are: normalcy, deterioration, adaptation, recovery, and growth. The paper then discusses the application of the revised Leader Resilience Profile® (LRP) data, comparing leader resilience according to gender and age. Results from this ongoing study on resilience clearly show as people age, their resilience increases. The 60+ age group, in particular, had significantly higher resilience scores than participants in other age groups. Men between the ages of 20-29 had significantly higher resilience scores than women of the same age group. Other age groups provided no notable differences or substantial correlations when it came to gender and age. A framework has been developed is presented for how to become more resilient as a person ages throughout the life course. This framework includes positive well-being, assessing and strengthening meaningful intrinsic and extrinsic resources, self-efficacy, future-focus, and important strategic avenues for resilient aging. The paper then raises the questions: who ages resiliently, and how, and what differences are there between young, old, retired, and elderly individuals when it comes to living and working resiliently? The paper concludes that with the following: support and proactivity are the means for achieving positive growth orientation, quality of life, self-identity, purpose, inhibiting stress-related debilitation, and resilient aging.